The construction of technique and tactic knowledge base in competitive sports - Wang, J.; Yu, L. J.; Zhang, H.; Zhang, L. L.; Song, C. H. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Starting from the proccsses of acquisition, representation, formation and reasoning of technique and tactic knowledge, the present paper discusses the construction process of the technique and tactic knowledge base in Sports (TTKB) and finally constructs the technique and tactic: knowledge base model, providing support for competitive technique and tactic analysis and decision making.